Status Terinfeksi Ektoparasit pada Kucing Kampung (Felis silvestris catus) Liar di Desa Waru Barat Kota Pamekasan - Ruspeni Daesusi; Anindita Riest Retno Arimurti; Gazi Fahriza; Asy'ari Asy'ari (PEDAGO BIOLOGI, 2022)
Ectoparasites are parasites that infest the body surface of cats. Ectoparasites interfere with the health of the main host, such as skin diseases, anemia, hypersensitivity disorders, dermatitis and as vectors of disease transmission. Ectoparasites are also zoonotic in which their effects cause harm to humans. Ectoparasites in cats can be transmitted to humans during cat-human interactions. Some of the ectoparasites that have symbiosis with cats are fleas, mites, ticks, and fleas. The purpose of this study was to determine the status of ectoparasite infection in feral cats in the Waru Barat area of Pamekasan City. This research is descriptive. The sampling method used accidental sampling with a sample of 18 wild cats (Felis silvestris catus) in Waru Barat Village, Pamekasan City. Based on the results of research on wild cats (Felis silvestris catus) in Waru Barat Village, Pamekasan City, it was concluded that as many as 18 samples (100%) were infected with ectoparasites. The type of ectoparasite that infects is the flea (Ctenocephalides felis).